Ancient introgression underlying the unusual mito‐nuclear discordance and coat phenotypic variation in the Moupin pika. (1st February 2022) - Ge, Deyan; Feijó, Anderson; Wen, Zhixin; Lissovsky, Andrey; Zhang, Dezhi; Cheng, Jilong; Yan, Chaochao; Mu, Danping; Wu, Xinlai; Xia, Lin; Yang, Qisen
Abstract: Aim: The mechanisms by which global biodiversity hotspots harbour and conserve high genetic and morphological diversity of endemic species remain unexplored. Relic species of ochotonids in the genus Ochotona are confined to alpine habitats and highly sensitive to environmental changes. We studied the genomic and ecological mechanisms underlying the divergence and adaptive evolution of the Moupin pika ( O. thibetana ) and its closely related species to infer its diversification, adaptive evolution and demographic history in response to historical and recent environmental changes. Location: Hengduan Mountain Region, China. Methods: We integrated morphological, genomic and ecological data to interpret the phylogeographic structure, adaptive evolution, demographic history and range shift of O. thibetana . Phylogenetic reconstruction was based on Cytochrome b ( CYTB ), the mitochondrial genome and single‐copy orthologues of the whole genome. Gene flow among extant lineages, as well as from extinct species, was inferred by multiple algorithms. Demographic history was inferred using the pairwise sequential Markovian coalescent and high‐resolution analysis of linkage disequilibrium. We also predicted the range shift of this species by using ecological niche modelling. Results: Phylogenetic reconstruction revealed an unusual mitochondrial lineage of O. thibetana from the western Sichuan Basin, which was named O. qionglaiensis in previous studies. Extensive gene flow was detected among genetic lineages of O. thibetana, which has distinct phenotypic variation in hair thickness and colouration, as well as notable morphological differentiation in external and craniodental measurements. Multiple members of the keratin gene family were identified as introgressed loci from some ancient species to O. thibetana . The Moupin pika underwent dramatic population shrinkage in the late Quaternary, with a clear trend of population growth in approximately the last 70 generations. The potential distribution range of O. thibetana showed a clear trend of expansion in the future. Main conclusions: The unusual mitochondrial phylogenetic pattern of O. thibetana resulted from "extended ghost introgression, " a new evolutionary model proposed in the present study, and thus rejected the validity of O. qionglaiensis as an independent species. Ancient introgression of keratin genes likely underlies the prominent coat phenotypic variation among genetic lineages. Clear population growth and range expansion of the Moupin pika in recent generations probably benefitted from recent global warming and vegetation recovery, which not only contributed to the conservation of large mammals but was also beneficial to small mammals endemic to alpine habitats.